2010
DOI: 10.1016/j.jasms.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the site of protein-ATP binding by top-down mass spectrometry

Abstract: A Fourier-transform ion cyclotron resonance (FT-ICR) top-down mass spectrometry strategy for determining the adenosine triphosphate (ATP)-binding site on chicken adenylate kinase is described. Noncovalent protein-ligand complexes are readily detected by electrospray ionization mass spectrometry (ESI-MS), but the ability to detect protein-ligand complexes depends on their stability in the gas phase. Previously, we showed that collisionally activated dissociation (CAD) of protein-nucleotide triphosphate complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 56 publications
7
104
0
Order By: Relevance
“…ECD-MS/MS of protein: ligand complexes yields fragments or product ions of the protein chain, some of which are still bound to the ligand. The sequence of these ligand-bound fragments can be mapped onto the full-length protein sequence to determine the ligand binding region(s) (15)(16)(17). This strategy was used previously to measure the binding of CLR01 to amyloid ␤-protein (18) and therefore we applied ESI-MS/MS with ECD here to determine the sites of CLR01 binding to ␣-synuclein.…”
Section: Resultsmentioning
confidence: 99%
“…ECD-MS/MS of protein: ligand complexes yields fragments or product ions of the protein chain, some of which are still bound to the ligand. The sequence of these ligand-bound fragments can be mapped onto the full-length protein sequence to determine the ligand binding region(s) (15)(16)(17). This strategy was used previously to measure the binding of CLR01 to amyloid ␤-protein (18) and therefore we applied ESI-MS/MS with ECD here to determine the sites of CLR01 binding to ␣-synuclein.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the use of ESI for transferring noncovalent complexes from solution into the gas phase for interrogation by ECD [22][23][24][25][26][27]. However, structural analysis using gas-phase dissociation techniques such as ECD can only provide accurate information about the solution binding sites if the gas-phase structure does not undergo significant structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ECD has been shown in many cases to preferentially cleave the protein backbone without disruption of noncovalent interactions [20,21]. This technique has been successfully applied in the localization of binding sites for several noncovalent complexes [22][23][24][25][26][27]. In each of these studies, the gas-phase results have matched closely with previous solution-phase studies on the complexes, thus the use of ECD for structural determination of non-covalent complexes has shown great promise.…”
mentioning
confidence: 83%
“…With this approach, the identification of peptide fragments retaining the ligand serves to localize the binding site(s). To date, binding sites of several protein-ligand complexes [11][12][13][14][15][16][17], including α-synuclein-spermine [15], adenylate kinase-ATP [16], and anterior gradient-2-PTTIYY hexapeptide interactions [17], were identified using this approach.…”
Section: Introductionmentioning
confidence: 99%